Penerapan Perilaku Hidup Bersih dan Sehat pada Karyawan Embung Persemaian di Kota Tarakan - Maria Selviana Joni; Vincentia Ade Rizky; Umi Latifah; Tri Astuti Sugiyatmi (Jurnal Kabar Masyarakat, 2026)
Clean and Healthy Living Behavior (PHBS) is a promotive and preventive effort that aims to improve the degree of public health through behavior change. Nursery reservoir employees have a high risk of exposure to the work environment in the form of dirty water, biological waste, and pathogenic microorganisms. This community service activity was carried out to increase the knowledge and practice of PHBS among employees of the nursery reservoir in Juata Tarakan based on national PHBS indicators. The implementation method includes counseling, demonstration, and evaluation using pre-test and post-test. The results showed a significant increase in employee knowledge, with an average pre-test score of 58.7 increasing to 78.3 in the post-test. The statistical test resulted in a value of p = 0.000 (p < 0.05), which confirms the effectiveness of PHBS educational interventions in improving workers' health knowledge and behavior. These findings provide practical implications that counseling-based education and demonstrations can be an effective strategy in encouraging the implementation of PHBS in risky work environments. Thus, this activity is expected to be able to support the creation of a healthier work environment, increase productivity, and become a model for community-based occupational health interventions.